Production of Angiotensin Converting Enzyme Inhibitory Peptides from Red Tilapia Protein Hydrolysates - Shamloo, Maryam (2010)
Fish proteins are considered as valuable nutrient and a good source of many bioactive peptides such as angiotensin converting enzyme (ACE) inhibitory peptides. Very few reports are available on the ACE inhibitory peptides in freshwater fish hydrolysates. Therefore, this study was carried out with the objective to produce tilapia protein hydrolysates by commercial proteases, named Alcalase, Flavourzyme and Protamex, investigating the ACE (Angiotensin Converting Enzyme) inhibitory activity, the radical scavenging ability and identifing the best enzyme to produce the highest bioactivity; optimizing the production of ACE inhibitory peptides using response surface methodology (RSM); and to fractionate the ACE inhibitory peptides using ultrafiltration membranes. The ACE inhibitory activities were determined using an in vitro method and the IC50 (peptide concentration which reduced ACE inhibitory by 50%) was calculated. The result indicated that Alcalase was the best enzyme to produce tilapia hydrolysates since it had the highest ACE inhibitory activity when compared to Protamex and Flavourzyme. A central composite design (CCD) involving 16 cube points, 8 axial points and 7 center points was employed to study the effect of temperature, time, pH and enzyme-substrate ratio on Alcalase hydrolytic activity. The combined level of 55.8 °C, 259.99 min, pH 7.5 and enzyme-substrate ratio of 3.58 % (w/w) was predicted to provide the most desirable bioactivity, which produce high ACE inhibitory activity in tilapia hydrolysates. The coefficient of determination value (R2) was 0.883 for the experimental data, which indicated a satisfactory adjustment of the reduced response models. The time, temperature and enzyme-substrate ratio of the hydrolysis had significant (p < 0.01) effects on the ACE inhibitory activity in tilapia hydrolysates. The most desirable hydrolysates were fractionated using three different molecular weight cut-off membranes (10 kDa, 5 kDa and 2 kDa). Four fractions (> 10 kDa, 10-5 kDa, 5-2 kDa and < 2 kDa) obtained had the ACE inhibitory activity, however, the fraction with molecular weight of < 2 kDa, appeared to have a significantly (p < 0.05) lower IC50 compared to the unfractionated hydrolysate, and the other fraction